Effect of ACL Graft Type on Side-Step Cutting in Young Athletes. Issue 7 (18th July 2016) - Pace, James Lee; Mueske, Nicole; Padilla, Ricardo A.; Katzel, Mia; Healy, Bitte S.; Wren, Tishya
Objectives: Due to the slightly higher re-tear rate for ACL reconstruction (ACLR) with hamstring (HT) versus patellar tendon (PT), differences in movement strategies were assessed during side-step cutting in young athletes with recent ACLR to determine if graft type affected post-operative motion. Methods: Dominant limbs from 21 athletes without lower extremity injury or previous surgery (age 14.9 ± 2.0 years) and 26 limbs with recent (5.1-8.0 months post-operative) unilateral ACLR were included, 18 with HT grafts (age 16.6 ± 3.7 years) and 8 with PT (age 16.7 ± 1.2 years). Lower extremity 3-dimensional data was recorded during the deceleration phase (initial contact to maximum knee flexion) of a 45° cut. Group differences were assessed using analysis of variance with Bonferroni post-hoc tests. Results: The HT group had a slower approach velocity than controls (2.9 vs. 3.5 m/s; p=0.006) with intermediate velocity in the PT group (3.2 m/s). Both the HT and PT groups had lower peak ground reaction force (GRF) compared to controls (HT: 2.0 body weights, PT: 2.2 BW, Control: 2.8 BW; p≤0.02), along with lower peak knee flexion moments (HT: 1.4 Nm/kg, PT: 1.3 Nm/kg, Control: 2.2 Nm/kg; p=0.002). The PT group had less power absorption at the knee than controls (0.3 vs. 0.7 Nm/kg; p=0.07), while the HT group had more at the hip (0.4 vs. 0.1 Nm/kg; p=0.04). The HT group also had higher peak hip flexion (HT: 65.8°, PT: 53.9°, Control: 55.1°; p≤0.06) and hip sagittal plane excursion (HT: 9.4°, PT: 3.6°, Control: 2.8°; p≤0.05) than the PT and control groups. The HT group had lower peak knee valgus moments than controls (0.05 vs. 1.2 Nm/kg; p=0.01) as well as a greater range of frontal plane pelvic (8.2° vs. 3.4°; p=0.03) and hip (7.6° vs. 3.0°; p=0.05) motion. The PT group had intermediate values for valgus moment (0.8 Nm/kg) and pelvic (4.9°) and hip (3.3°) excursion. Conclusion: While both ACLR groups showed reduced GRFs and knee flexion moments compared with controls, the HT group demonstrated greater adaptations proximally with increased hip flexion and frontal plane pelvic and hip excursion. The lower frontal and sagittal plane hip motion in the PT group may be due to anterior knee pain associated with PT grafts. Since the HT group exhibited movement adaptations, but no observable pathologic movement patterns, such as increased knee valgus moment, other factors likely account for the observed higher re-tear rate in HT vs. PT ACLR.